2023
DOI: 10.1037/ebs0000294
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescents’ involvement in anonymous relational and cyber aggression: An evolutionary perspective.

Abstract: This study used an evolutionary psychological perspective to investigate early adolescents' involvement in indirect relational and cyber aggression that was perpetrated anonymously. Relations with the functions and targets of aggression, and victims' perceptions of harm, were examined to consider whether anonymous indirect aggression may be used selectively in a manner that could be conditionally adaptive. In a sample of 378 students (11-14 years; M = 12.87, SD = .84), anonymous aggression was most consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 104 publications
(273 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, the contextual features of CMC perpetuate pluralistic ignorance in bystanders' nonintervention. In an online environment where visual anonymity and group norms are salient, individuals are more willing to conform to a group norm rather than insisting on their individual beliefs (Lapierre & Dane, 2022;Wingate et al, 2013). In addition, the most common type of cyberbullying is verbal and is often mis-conceptualized and mis-rationalized by witnesses as a "mild" form of bullying in the anonymous online environment.…”
Section: Group Norm Misinterpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the contextual features of CMC perpetuate pluralistic ignorance in bystanders' nonintervention. In an online environment where visual anonymity and group norms are salient, individuals are more willing to conform to a group norm rather than insisting on their individual beliefs (Lapierre & Dane, 2022;Wingate et al, 2013). In addition, the most common type of cyberbullying is verbal and is often mis-conceptualized and mis-rationalized by witnesses as a "mild" form of bullying in the anonymous online environment.…”
Section: Group Norm Misinterpretationmentioning
confidence: 99%
“…In addition, the most common type of cyberbullying is verbal and is often mis-conceptualized and mis-rationalized by witnesses as a "mild" form of bullying in the anonymous online environment. Because witnesses cannot see the facial expressions of others, it is difficult to evaluate the exact feelings of victims and other witnesses about the verbal attack (Rivers & Smith, 1994), so once the witnesses perceive that no one has reacted to the cyberbullying, they may assume that nonintervention is a normative response (Lapierre & Dane, 2022;Wingate et al, 2013).…”
Section: Group Norm Misinterpretationmentioning
confidence: 99%
“…Although risky, aggression against high-status victims has been shown to yield substantial rewards, with aggression against more prestigious targets being associated with greater social prestige gains than aggression directed toward less prestigious individuals (Andrews et al, 2017). Furthermore, indirect forms of attack may minimize the risk of adversarial aggression (e.g., Lapierre & Dane, 2023). Therefore, in accordance with evolutionary perspectives, adolescents may inflict costs on rivals of equal or greater power (e.g., derogate to damage reputations) to compete for evolutionarily relevant and highly valued social resources such as dominance, status, or dating opportunities (Buss & Shackelford, 1997; Dane et al, 2022; Dawes & Malamut, 2020; Morgan et al, 2022).…”
mentioning
confidence: 99%
“…Consequently, the vast majority of past research on victimization has not differentiated being bullied from victimization perpetrated by an individual with equal or less power than the victim. The latter has been called adversarial victimization , as the targets appear to be selected due to competition and rivalry (Dane et al, 2022; Lapierre & Dane, 2022, 2023 see Figure 1). Recent research, albeit scant, has shown that adversarial victimization is associated with aggressive competition against rivals as well as aggression and victimization by anonymous perpetrators (Dane et al, 2022; Lapierre & Dane, 2022, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation